Analysis of Socio-Culture for the Use of Instagram among Students - Fungsihan, Indy; Rasyida, Khalida Izdihar; Amalinda, Kiki Rizki; Kusumadyahdewi, Kusumadyahdewi; Rohmah, Ni’matu (Letters in Information Technology Education (LITE), 2019)
The use of Instagram from only sharing photos or videos and interacting with users has become a place for personal branding such as business events, information sources, and publications to get appreciation. Among students, the purpose of using Instagram can also change from the purpose of initial account creation. Different goals can be influenced by the needs and suitability of media content. To examine the socio-culture of Instagram usage patterns among students, research was conducted using a data collection method using a questionnaire. The results show the suitability of content and objectives do not affect the intensity of use, but affect the intensity of data upload. Appropriateness of content affects the choice of Instagram users to take advantage of privacy features. Based on these two things, it can be concluded that the intensity and use of privacy features affect personal branding, because the intensity of the influence of the level of communication of users with the audience, while the use of privacy features will affect the level of audience curiosity towards user data.